Molecular Characterisation of Escherichia Coli Isolated from Raw Milk and Village Chicken and Broiler Litter - Lihan, Samuel (1999)
Thirty five litter samples of village chickens, 35 broilers and 32 samples of raw milk were examined for the presence of E. coli. All samples were positive for E. coli. Three hundred and five isolates of E. coli were isolated from litter samples of village chickens (105 isolates), broilers (105 isolates) and raw milk samples (95 isolates). All the isolates were examined for antibiotic resistance, plasmid profiles and polymorphism using random amplification of polymorphic DNA (RAPD) analysis. Isolates isolated from litter of village chickens and broilers had a multiple antibiotic resistance (MAR) index of 0.31 to 0.75 and 0.44 to 0.69, respectively. Isolates isolated from raw milk had a MAR index of 0.31 to 0.88. High MAR index suggests that all the isolates originated from high risk sources. The E. coli isolates isolated from village chickens, broilers and raw milk samples were grouped into 34,30 and 28 distinct antibiotypes, respectively. Eighty (76.2%) and 99 (94.3%) isolates were found to harbour plasmids ranging in size from 1.2 to 64 MDa and 1.2 to 80 MDa among isolates isolated from village chickens and broilers, respectively. Isolates isolated from raw milk harboured plasmids ranging in size from 1.4 to 68 MDa. Based on their plasmid profiles, the E. coli isolates isolated from village chickens, broilers and raw milk were grouped into 28, 57 and 5 plasmid patterns, respectively. Three l0-mer oligonucleotides primers (Gen1-50-02, Gen1-50-09 and Gen1-50-10) were used to amplify genomic DNA. The profiles observed after electrophoretic separation for the three primers when combined together were able to distinguish the E. coli isolates from village chickens, broilers and raw milk into 92, 96 and 50 RAPD patterns, respectively. The large number of subgroups within these isolates indicates that there is a high degree of diversity within E. coli isolates, isolated from village chickens, broilers and raw milk samples. Isolates, isolated from village chickens, broilers and raw milk are genotypically diverse as shown by RAPD pattern, suggesting that different strains have been brought into the geographic region and strains already present have continued to evolve. These results suggest that RAPD-PCR assay is more discriminating than plasmid profiling and antibiotyping, and could be a valuable tool for epidemiological studies.